KORELASI ANTARA PEMANFAATAN FASILITAS PRAKTIK DAN MINAT SISWA DENGAN HASIL BELAJAR SISWA SMK MUHAMMADIYAH SURUH KABUPATEN SEMARANG - Muhamad Suswanto; Pairun Roniwijaya (Universitas Sarjanawiyata Tamansiswa, 2015)
The main purpose of this research was to understand about correlate between of practical facility utilization and students interest with students achievement on automotive electrical base. This research was ex-post facto. The population of this research was students of class X TKR SMK Muhammadiyah Suruh Kecamatan Suruh Kabupaten Semarang at year of 2014/2015. The sample was determined by proportional random sampling. Data was collected by using questionnaire and documentation. Data was analyzed by descriptive analysis and bicorrelation analysis. Prerequisite analysis test were normality test, linierity test and multicolinierity test. The result of this research indicated that: there is a positive and significantly correlation between of practical facility utilization with students achievement were and coefficient of partial correlation ; there is a positive and significantly correlation between of students interest with students achievement were and coefficient of partial correlation ; there is a positive and significantly correlation between of practical facility utilization and students interest with students achievement were and coefficient of bicorrelation . practical facility utilization and students interest contributing simultaneously and significantly with students achievement by .